Animal suffering in factory farming and the best way to prevent it - Watkins, Gareth (Rhodes University, Faculty of Humanities, Department of Philosophy, 2005)
This thesis moves beyond the traditional approaches of how we ought to treat animals, and instead concentrates on the best strategy for preventing animal suffering in the farming industry. Chapter 1 considers the question of how we can know that animals feel pain, and concludes not only that it is rational to believe that they can, but also that this is a significant fact. Chapter 2 then analyses one possible strategy for helping to prevent animal suffering, namely demi-vegetarianism. For a number of reasons, however, this strategy is found to be flawed, therefore Chapter 3 analyses a second possible strategy, namely vegetarianism, and concludes that this is, in fact, the best strategy for helping to prevent animal suffering in the farming industry.
Keywords: Vegetarianism -- Moral and ethical aspects; Food animals -- Moral and ethical aspects; Animal rights; Animal welfare; Animal welfare -- Moral and ethical aspects; Vegetarianism